Memperjuangkan Kasih Sayang Dan Cinta Sesama Jenis: Semiotika Budaya Terhadap Film Monster - Sunaryanto, Sunaryanto; Adnan, Ahmad; Mufidah, Nur (Gandiwa Jurnal Komunikasi, 2025)
The construction of homosexual identity in film is shaped through the representation of values, rituals, heroes, and symbols. Values are constructed through the deconstruction of dominant worldviews that regard homosexual identity as deviant, while rituals are portrayed to normalize such behavior within the film’s narrative. Heroes and symbols serve as visual and narrative representations that reinforce identity and demonstrate the equality of homosexual individuals with heterosexual groups This study aims to critically analyze the meaning of affection and love as advocated by homosexual groups in the film Monster (2023). The research method employed is qualitative with a textual analysis of mass media. Data analysis uses Roland Barthes' semiotics, consisting of denotation, connotation, and myth. Barthes' semiotics is then integrated with Hofstede’s cultural theory, which includes values, rituals, heroes, and symbols. The findings conclude that Monster (2023) represents the struggle of gay individuals to express affection and love through subtle yet meaningful symbolic signs such as gazes, caresses, embraces, and flowers. On the levels of connotation and myth, the film challenges heteronormative norms by asserting that love and happiness are universal rights not limited to heterosexual relationships. Through the value of “our future,” youth social rituals, heroic figures, and queer identity symbols, the film constructs a narrative of acceptance toward same-sex relationships.